Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

Towards a disease digital twin: Howard T. Odum's legacy for cancer biology and medicine - F. Surra; L. Conte; E. Cavarzerani; F. Rizzolio; A. Romano; F. Gonella (Ecological Modelling, 2025)

Modelling the population dynamics of Rift Valley fever virus mosquito vectors in the western Mediterranean Basin - Alex Drouin; Thomas Balenghien; Benoit Durand; Carles Aranda; Amal Bennouna; Ali Bouattour; Said C Boubidi; Annamaria Conte; Sarah Delacour; Maria Goffredo; Oumnia Himmi; Grégory L'Ambert; et al. (Ecological Modelling, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Hazardous element inertisation in vitrified silicate ceramics: Effect of different matrices - S. Conte; C. Molinari; M. Ardit; L. Mantovani; M. Tribaudino; G. Cruciani; M. Dondi; C. Zanelli (Journal of Hazardous Materials, 2024)

Factors related to longevity and mortality of dogs in Italy - Mariana Roccaro; Romolo Salini; Marco Pietra; Micaela Sgorbini; Eleonora Gori; Maurizio Dondi; Paolo E. Crisi; Annamaria Conte; Paolo Dalla Villa; Michele Podaliri; Paolo Ciaramella; Cristina Di Palma; et al. (Preventive Veterinary Medicine, 2024)

SPORA, a new silver phosphate precipitation protocol for oxygen isotope analysis of small, organic-rich bioapatite samples - Gabriele Larocca Conte; Lauren E. Lopes; Aric H. Mine; Robin B. Trayler; Sora L. Kim (Chemical Geology, 2024)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

A second locus contributing to the differential expression of the blue sensitive opsin SWS2A in Lake Malawi cichlids - Sri Pratima Nandamuri; Jane E. Schulte; Miranda R. Yourick; Benjamin A. Sandkam; Kristen A. Behrens; Melissa M. Schreiner; Maya Dayanim; Garrett Sweatt; Matthew A. Conte; Scott A. Juntti; Karen L. Carleton (Hydrobiologia, 2023)

Torrefaction as a Chlorine Reduction Process of Brazilian Eucalyptus sp. for Use as Biofuel - Erica L. Romão; Jean M. da Silva; Nicolas V. dos Santos Luz; Rosa A. Conte (BioEnergy Research, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Principles and applications of non-thermal technologies and alternative chemical compounds in meat and fish - Denes K. A. Rosario; Bruna L. Rodrigues; Patricia C. Bernardes; Carlos A. Conte-Junior (Critical Reviews in Food Science and Nutrition, 2021)

Movement of transposable elements contributes to cichlid diversity - Karen L. Carleton; Matthew A. Conte; Milan Malinsky; Sri Pratima Nandamuri; Benjamin A. Sandkam; Joana I. Meier; Salome Mwaiko; Ole Seehausen; Thomas D. Kocher (Molecular Ecology, 2020)
African cichlid fishes are a prime model for studying speciation mechanisms. Despite the development of extensive genomic resources, it has been difficult to determine which sources of genetic variation are responsible for cichlid phenotypic variation. One of their most variable phenotypes is visual sensitivity, with some of the largest spectral shifts among vertebrates. These shifts arise primarily from differential expression of seven cone opsin genes. By mapping expression quantitative trait loci (eQTL) in intergeneric crosses of Lake Malawi cichlids, we previously identified four causative genetic variants that correspond to indels in the promoters of either key transcription factors or an opsin gene. In this comprehensive study, we show that these indels are the result of the movement of transposable elements (TEs) that correlate with opsin expression variation across the Malawi flock. In tracking the evolutionary history of these particular indels, we found they are endemic to Lake Malawi, suggesting that these TEs are recently active and are segregating within the Malawi cichlid lineage. However, an independent indel has arisen at a similar genomic location in one locus outside of the Malawi flock. The convergence in TE movement suggests these loci are primed for TE insertion and subsequent deletions. Increased TE mobility may be associated with interspecific hybridization, which disrupts mechanisms of TE suppression. This might provide a link between cichlid hybridization and accelerated regulatory variation. Overall, our study suggests that TEs may be an important driver of key regulatory changes, facilitating rapid phenotypic change and possibly speciation in African cichlids.

Correction to: Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Effect of Restraining the Base of Support on the Other Biomechanical Features in Patients with Cerebellar Ataxia - C. Conte; Mariano Serrao; L. Cuius; A. Ranavolo; S. Conforto; F. Pierelli; L. Padua (The Cerebellum, 2018)

Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen - Juliana C. Veit; Jaqueline Piccolo; Aline F. Scherer; Isadora S. Machado; Luana H. Maurer; Lisiane Conte; Bernardo Baldisserotto; Gessi Koakoski; Charlene C. Menezes; Vania L. Loro; Leonardo J. G. Barcellos; Berta M. Heinzmann; et al. (Journal of Aquatic Food Product Technology, 2018)

In situ remediation of contaminated marinesediment: an overview - G. Lofrano; G. Libralato; D. Minetto; S. De Gisi; F. Todaro; B. Conte; D. Calabrò; L. Quatraro; M. Notarnicola (Environmental Science and Pollution Research, 2017)

Tooth agenesis and orofacial clefting: genetic brothers in arms? - M. Phan; F. Conte; K. D. Khandelwal; C. W. Ockeloen; T. Bartzela; T. Kleefstra; H. van Bokhoven; M. Rubini; H. Zhou; C. E. L. Carels (Human Genetics, 2016)

The Ventotene Volcanic Ridge: a newly explored complex in the central Tyrrhenian Sea (Italy) - Marco Cuffaro; Eleonora Martorelli; Alessandro Bosman; Alessia Conti; Sabina Bigi; Filippo Muccini; Luca Cocchi; Marco Ligi; Giovanni Bortoluzzi; Davide Scrocca; Simonepietro Canese; Francesco L. Chiocci; et al. (Bulletin of Volcanology, 2016)

Systematic analysis of copy number variants of a large cohort of orofacial cleft patients identifies candidate genes for orofacial clefts - Federica Conte; Martin Oti; Jill Dixon; Carine E. L. Carels; Michele Rubini; Huiqing Zhou (Human Genetics, 2016)

Comparative analysis of nutritional compositions of transgenic RNAi-mediated virus-resistant bean (event EMB-PV051-1) with its non-transgenic counterpart - José L. V. Carvalho; Juliana de Oliveira Santos; Carmine Conte; Sidney Pacheco; Elsa O. P. L. Nogueira; Thiago L. P. O. Souza; Josias C. Faria; Francisco J. L. Aragão (Transgenic Research, 2015)

Depth-dependent photodegradation of marine dissolved organic matter - Stephen A. Timko; Anastasia Maydanov; Sandra L. Pittelli; Maureen H. Conte; William J. Cooper; Boris P. Koch; Philippe Schmitt-Kopplin; Michael Gonsior (Frontiers in Marine Science, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Photonic efficiency of the photodegradation of paracetamol in water by the photo-Fenton process - E. Yamal-Turbay; E. Ortega; L. O. Conte; M. Graells; H. D. Mansilla; O. M. Alfano; M. Pérez-Moya (Environmental Science and Pollution Research, 2015)

Genetic diversity of the rare and endangered meadow violet ( Viola pumila Chaix) at the southern margin of its range - F. Buldrini; L. Conte; D. Dallai; C. Ferrari (Plant Biosystems, 2013)

Plasmid-mediated fluoroquinolone resistance determinants in Escherichia coli from community uncomplicated urinary tract infection in an area of high prevalence of quinolone resistance - C. Longhi; M. P. Conte; M. Marazzato; V. Iebba; V. Totino; F. Santangelo; C. Gallinelli; L. Pallecchi; E. Riccobono; S. Schippa; A. Comanducci (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Pallidothalamic-projecting neurons in Macaca fascicularis co-express GABAergic and glutamatergic markers as seen in control, MPTP-treated and dyskinetic monkeys - Lorena Conte-Perales; Alberto J. Rico; Pedro Barroso-Chinea; Virginia Gómez-Bautista; Elvira Roda; Natasha Luquin; Salvador Sierra; José L. Lanciego (Brain Structure and Function, 2011)

Glutamatergic and cholinergic pedunculopontine neurons innervate the thalamic parafascicular nucleus in rats: changes following experimental parkinsonism - Pedro Barroso-Chinea; Alberto J. Rico; Lorena Conte-Perales; Virginia Gómez-Bautista; Natasha Luquin; Salvador Sierra; Elvira Roda; José L. Lanciego (Brain Structure and Function, 2011)

Isolation and characterization of polymorphic microsatellites for the natural populations of barker frog Physalaemus cuvieri - M. Conte; L. J. Cançado; P. R. Laborda; M. I. Zucchi; G. V. Andrade; D. C. Rossa-Feres; S. Siqueira; A. P. Souza; S. M. Recco-Pimentel (Conservation Genetics, 2009)

The efficacy of the fluorescent conjugates of cholera toxin subunit B for multiple retrograde tract tracing in the central nervous system - William L. Conte; Hiroaki Kamishina; Roger L. Reep (Brain Structure and Function, 2009)

Determination of polycyclic aromatic hydrocarbons (PAHs) in commonly consumed Nigerian smoked/grilled fish and meat - V.O.E. Akpambang; G. Purcaro; L. Lajide; I.A. Amoo; L.S. Conte; S. Moret (Food Additives & Contaminants: Part A, 2009)

A single insemination intervention in the sow with barium alginate-encapsulated boar semen - M. Faustini; A. Riccardi; S. Villani; V. Russo; M. L. Torre; U. Conte; D. Vigo (Veterinary Research Communications, 2008)

Organochlorine pesticides and polychlorinated biphenyl residues in reared and wild Dicentrarchus labrax from the Mediterranean Sea (Sicily, Italy) - V. Lo Turco; G. Di Bella; L. La Pera; F. Conte; B. Macrí; G. mo Dugo (Environmental Monitoring and Assessment, 2007)

The “in situ” expression of Human Leukocyte Antigen Class I antigens is not altered by cryopreservation in human arterial allografts - G. Pasquinelli; M. P. Pistillo; F. Ricci; M. Buzzi; P. L. Tazzari; L. Foroni; C. Manferdini; C. Ceccarelli; A. Stella; R. Conte (Cell and Tissue Banking, 2007)

Genetic and phytochemical difference between some Indian and Italian plants of Withania somnifera (L.) Dunal - P Scartezzini; F Antognoni; L Conte; A Maxia; A Troìa; F Poli (Natural Product Research, 2007)

Competence of Swine Oocytes Matured by Three-dimensional Gonadotropin-free Co-culture - E. Munari; A. Asti; C. Colombani; E. Benzoni; M. Faustini; M. L. Torre; A. Riccardi; S. Villani; L. Sesso; U. Conte; D. Vigo (Veterinary Research Communications, 2007)

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - L. Conte; C. Cotti; G. Cristofolini (Plant Biosystems, 2007)

Effects of 5 Hz subthreshold magnetic stimulation of primary motor cortex on fast finger movements in normal subjects - R. Agostino; E. Iezzi; L. Dinapoli; F. Gilio; A. Conte; F. Mari; A. Berardelli (Experimental Brain Research, 2007)

Pheromone Communication in the Honeybee (Apis mellifera L.) - Keith N. Slessor; Mark L. Winston; Yves Le Conte (Journal of Chemical Ecology, 2005)

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation - A. Cappellini; P. L. Tazzari; I. Mantovani; A. M. Billi; C. Tassi; F. Ricci; R. Conte; A. M. Martelli (Apoptosis, 2005)

Detection of ephemeral genetic sub-structure in the narrow endemic Abies nebrodensis (Lojac.) Mattei (Pinaceae) using RAPD markers - L Conte; C Cotti; R Schicchi; FM Raimondo; G Cristofolini (Plant Biosystems, 2004)

Research on Bacteraemia in Cultured Rainbow Trout - A. Panebianco; A. Giuffrida; F. Conte; G. Ziino; A. Minniti; L. Iannuzzi (Veterinary Research Communications, 2004)

Fogging can control Tetranychus urticae on greenhouse cucumbers - C. Duso; F. Chiarini; L. Conte; V. Bonora; L. Dalla Mont; S. Otto (Journal of Pest Science, 2004)

Animal Transmissible Spongiform Encephalopathies and Genetics - U. Agrimi; M. Conte; L. Morelli; M.A. Di Bari; G. Di Guardo; C. Ligios; G. Antonucci; G.M. Aufiero; N. Pozzato; F. Mutinelli; R. Nonno; G. Vaccari (Veterinary Research Communications, 2003)

Spread of electrical activity at cortical level after repetitive magnetic stimulation in normal subjects - Lorenzano C.; Gilio F.; Inghilleri M.; Conte A.; Fofi L.; Manfredi M.; Berardelli A. (Experimental Brain Research, 2002)

Does the Spatial Distribution of the Parasitic Mite Varroa jacobsoni Oud. (Mesostigmata: Varroidae) in Worker Brood of Honey Bee Apis Mellifera L. (Hymenoptera: Apidae) Rely on an Aggregative Process? - M. Salvy; Y. Capowiez; Y. Le Conte; M. Salvy; J.-L. Clément (The Science of Nature, 1999)

Genetic diversity in Cytisus aeolicus Guss. ( Leguminosae ), a rare endemite of the Italian flora - L. CONTE; A. TROÍA; G. CRISTOFOLINI (Plant Biosystems, 1998)

Isolation and biodiversity in Cytisus villosus Pourret (Fabaceae, Genisteae): enzyme polymorphism in disjunct populations - A. TROÍA; L. CONTE; G. CRISTOFOLINI (Plant Biosystems, 1997)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)